2005
DOI: 10.1182/blood.v106.11.3740.3740
|View full text |Cite
|
Sign up to set email alerts
|

New Reference Ranges in Haematology for Healthy Adults Using the Modern Sysmex XE-2100 Automated Analyser.

Abstract: Establishing clearly defined, accurate reference ranges facilitates good interpretation and effective discrimination between health and disease. These can be used to obviate the need for unnecessary follow-up medical examinations thereby reducing costs. Our data represent findings from one of the most comprehensive studies ever undertaken with the XE-2100 to establish reference ranges (RRs) in healthy adults. Early morning venous samples were collected into Greiner EDTA Vacuettes (Ref: 454286) from 221 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Determination of alterations in these parameters was based on the reference intervals established for each test ( Table A1 ). 18 , 19 , 20 , 21 , 22 All the hematological and biochemical exams were performed using automated equipment, following the standards of laboratory quality control (Pentra 80 Hematology Counter Horiba Medical, Montpellier, France; and CT 600i Automated Analyzer Wiener Laboratories, Rosario, Argentina).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Determination of alterations in these parameters was based on the reference intervals established for each test ( Table A1 ). 18 , 19 , 20 , 21 , 22 All the hematological and biochemical exams were performed using automated equipment, following the standards of laboratory quality control (Pentra 80 Hematology Counter Horiba Medical, Montpellier, France; and CT 600i Automated Analyzer Wiener Laboratories, Rosario, Argentina).…”
Section: Methodsmentioning
confidence: 99%
“…The cutoff point of each parameter for change identification was established within the normal range limits. 18 , 19 , 20 , 21 , 22 The proportion of patients with values above or below the selected cut-off point was compared between the groups of acute and convalescent phases of vivax malaria. This analysis was performed in a 2 × 2 table and the results of chi-square test and the 95% confidence interval of the odds ratio were compared between the groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did a complete blood count which showed a significant low hemoglobin-7.1 g/dL (biological reference interval: 12-15.2 g/dL) with microcytosis-MCV of 59.6 fL (biological reference interval: 85-98 fL). 7 This was followed with a blood smear study which showed numerous target cells and schistiocytes. Based on these findings, we have arrived at a laboratory diagnosis of HbE homozygous with β-thalassemia, 8 though confirmation demanded molecular studies which could not be proceeded due to unavailability of resources.…”
Section: Taskmentioning
confidence: 99%